1993
DOI: 10.1063/1.354947
|View full text |Cite
|
Sign up to set email alerts
|

Controlling strength and toughness of multilayer films: A new multiscalar approach

Abstract: Multiscalar films are produced in order to combine both toughness and strength into a multilayer film. These structures incorporate both a strengthening phase and a toughening phase in a compositionally modulated microcomposite. The mechanical properties and microstructure for thick (-50 pm> MO/W multiscalar films have been characterized. A detailed microstructural analysis (including transmission electron microscopy, scanning electron microscopy, and x-ray techniques) of MO/W multiscalar ftlms has shown that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…A rough growth surface can lead to a decreased film density when voids form along columnar grain boundaries as a result of self-shadowing [96]. Deposition onto a severely roughened surface can further result in a distribution of reactant layer thicknesses rather than the single, intended value for each reactant [73].…”
Section: Properties Of As-deposited Multilayers (Prior To Ignition)mentioning
confidence: 98%
“…A rough growth surface can lead to a decreased film density when voids form along columnar grain boundaries as a result of self-shadowing [96]. Deposition onto a severely roughened surface can further result in a distribution of reactant layer thicknesses rather than the single, intended value for each reactant [73].…”
Section: Properties Of As-deposited Multilayers (Prior To Ignition)mentioning
confidence: 98%
“…Since the 1980s, fundamental research has been carried out on these LMCs and it was shown that the internal material interfaces play an important role on the monotonic and cyclic mechanical properties. The monotonic strength of LMCs is significantly higher than that of the mono‐material reference sheets, if the layer thickness is in the sub‐micron range . Under cyclic loading, a pronounced crack bifurcation at the material interface is the key to prolonged fatigue lives .…”
Section: Introductionmentioning
confidence: 99%
“…Sputter-deposited metallic thin films are used heavily in the semiconductor [1,2], magnetic recording media [3], and wear-resistant coatings industries [4]. For this reason, any study showing how to better control the microstructural evolution in these layers is of interest.…”
Section: Introductionmentioning
confidence: 99%